In‐Plane Micro‐Supercapacitors for an Integrated Device on One Piece of Paper. (14th September 2017) - Guo, Ruisheng; Chen, Jiangtao; Yang, Bingjun; Liu, Lingyang; Su, Lijun; Shen, Baoshou; Yan, Xingbin
Abstract: Portable and wearable sensors have attracted considerable attention in the healthcare field because they can be worn or implanted into a human body to monitor environmental information. However, sensors cannot work independently and require power. Flexible in‐plane micro‐supercapacitor (MSC) is a suitable power device that can be integrated with sensors on a single chip. Meanwhile, paper is an ideal flexible substrate because it is cheap and disposable and has a porous and rough surface that enhances interface adhesion with electronic devices. In this study, a new strategy to integrate MSCs, which have excellent electrochemical and mechanical performances, with sensors on a single piece of paper is proposed. The integration is achieved by printing Ni circuit on paper without using a precoating underlay. Ink diffusion is also addressed to some degree. Meanwhile, a UV sensor is integrated on a single paper, and the as‐integrated device shows good sensing and self‐powering capabilities. MSCs can also be integrated with a gas sensor on one‐piece paper and can be charged by connecting it to a solar cell. Thus, it is potentially feasible that a flexible paper can be used for integrating MSCs with solar cell and various sensors to generate, store, and use energy. Abstract : An integrated device that is composed of in‐plane micro‐supercapacitors (MSCs) and sensor on one piece of paper is fabricated based on screen‐printed Ni circuit for flexible and wearable electronics. The fabricated MSC shows excellent static and dynamic bending performances. The as‐integrated devices present good sensing responsibility and self‐powering capability.